Case of nasopharyngeal metastases presenting with multiple atypical cranial nerve deficits - Tiwari, Priyal; Renjen, Pushpendra Nath; Chaudhari, Dinesh Mohan (International Journal of Advances in Medicine, 2023)
Jugular foramen syndrome is an uncommon condition with a wide range of possible causes. We present a rare case of Villaret syndrome as an example of jugular foramen syndrome and illustrate a clinical-radiological approach for diagnosing jugular foramen syndrome. The morphological similarities between mesenchymal tumors such as rhabdomyosarcoma and phyllodes seen in our patient make immuno-histochemical (IHC) characterization essential for a definitive diagnosis. Jugular foramen syndromes, including Vernet syndrome, Collet Sicard, Villaret, Tapia, Jackson, and Schmidt, can manifest with multiple cranial nerve deficits in contiguous areas. In our case, the patient exhibited palate paralysis, pharyngeal anesthesia, and Horner's syndrome, thereby highlighting the differential diagnoses of Villaret syndrome and Tapia syndrome.